KAJIAN LAJU TRANSFOR SEDIMEN DI ESTUARIA JENEBERANG, STUDI KASUS PEMUNCULAN TOMBOLO AKTIF DI SELATAN ESTUARIA - Mustika, Andi Mega; Baeda, Achmad Yasir (Riset Sains dan Teknologi Kelautan, 2025)
Sediment movement continuously at the mouth of the river causing erosion and sedimentation and shoreline changes in thearea around the estuary. Introduction behavior sedimentation in the estuary is an important initial step in determining stepefforts to address the problem of sediment deposition and movement. This study aimed to determine the pattern of propagation of waves and currents and their effects on sediment and Tombolo active or cuspate appearance. The methodology used in data collection is to perform direct measurements and the data obtained is processed by software based on finite difference especially for the analysis of wave propagation patterns and sediment movements. The results of the study conducted in the southern estuaries Jeneberang shows that the propagation pattern of waves and currents affect the movement of sediment and the intersection between the two causes that trigger the appearance of sediment deposition on Tombolo active or cuspate.